Variations of the superior sagittal sinus and bridging veins in human dissections and computed tomography venography - Brockmann, Carolin; Kunze, Sandra Christiane; Schmiedek, Peter; Groden, Christoph; Scharf, Johann (Clinical imaging, 2012)
Objectives: The aim of the present study was to examine the superior sagittal sinus (SSS) and bridging veins (BVs) from an anatomical, neurosurgical and radiological perspective. Methods: Computed tomography venographies (CTVs) of 30 patients and 9 cadaveric dissections of human SSS were analyzed. Results: CTV and cadavers showed most BVs emptying into the SSS close by (±3 cm) and distal to the coronary suture (74% in CTV, 62% in cadavers). Conclusions: Important anatomical information can be drawn from cerebral CTV for neurosurgical preoperative planning.